2002
DOI: 10.1897/1551-5028(2002)021<1272:bmrfgf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bauxite Manufacturing Residues From Gardanne (France) and Portovesme (Italy) Exert Different Patterns of Pollution and Toxicity to Sea Urchin Embryos

Abstract: This study was designed to investigate the composition and toxicity of solid residues from bauxite manufacturing plants. Soil and dust samples were collected in the proximity of two bauxite plants (Gardanne, France, and Portovesme, Italy). Samples were analyzed for their content of some selected inorganic contaminants by means of inductively coupled plasma optical emission spectroscopy (ICP-OES) either following acid digestion procedures or by seawater release of soluble components. Toxicity was tested by sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…[12][13][14] The generation of M 1 dG adducts, a biomarker of oxidative stress and LPO, 18,[32][33][34][35] is promoted by a secondary reaction that may be induced by any reactive species capable of inducing oxidative stress. Therefore, the heavy metals emitted from the non-ferrous metallurgy estate 9,11 may also play a relevant role in the formation of exocyclic DNA adducts. For example, Cd is not redox-active, but it may induce increased levels of oxidative stress, possibly through the inhibitory effect on antioxidant enzymes, as well as by the inhibition of DNA-repair systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] The generation of M 1 dG adducts, a biomarker of oxidative stress and LPO, 18,[32][33][34][35] is promoted by a secondary reaction that may be induced by any reactive species capable of inducing oxidative stress. Therefore, the heavy metals emitted from the non-ferrous metallurgy estate 9,11 may also play a relevant role in the formation of exocyclic DNA adducts. For example, Cd is not redox-active, but it may induce increased levels of oxidative stress, possibly through the inhibitory effect on antioxidant enzymes, as well as by the inhibition of DNA-repair systems.…”
Section: Discussionmentioning
confidence: 99%
“…2 Adverse health effects, including clinical signs of fluorosis, have been associated with environmental exposure to fluoride in aluminum smelting and steel foundries, [3][4][5] as well as in the surrounding residential area. 7 A number of pollutants may be emitted from aluminum smelting complexes, including gaseous and particulate fluorides, 2,8 cadmium (Cd), lead (Pb), 9,10 formaldehyde and phenol, 11 that may cause adverse health effects for workers, 3 as well as people and domestic animals. 7 A number of pollutants may be emitted from aluminum smelting complexes, including gaseous and particulate fluorides, 2,8 cadmium (Cd), lead (Pb), 9,10 formaldehyde and phenol, 11 that may cause adverse health effects for workers, 3 as well as people and domestic animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…South-western Sardinia's mining areas produced about 15 Mton of metal, which makes the region comparable to Ireland in total metal production (Salminen et al, 2005). The cumulative impacts of environmental hazards in south-western Sardinia resulting from mining and industrial activities is well documented: on land (Leita et al, 1989;Caboi et al, 1993;Boni et al, 1999;ISS, 2002), in coastal areas (Caredda et al, 1999;Pagano et al, 2002), and in human health risk factors (Cardia et al, 1989;Sanna et al, 2002;Cocco et al, 1996). However, there is little information available on the impact of such factors on pelagic marine fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigating complex mixture-associated contamination and toxicity may provide direct information on the impact of anthropogenic pollution sources in environmental and human health (Chapman 2002). In previous studies, we had reported on toxicities of several complex mixtures, as environmentally-occurring and spiked marine and freshwater sediments (Pagano et al 1993; 2001a; Guillou et al 2000), industrial wastewater and contaminated soil (Trieff et al 1995; Pagano et al 1996; 2002a,b), and a pesticide formulation (Pagano et al 2001b).…”
Section: Introductionmentioning
confidence: 99%